Respuesta :
Answer:
-6
Step-by-step explanation:
2 - [6 ÷ 2 + {6 × 1/2 + (7/2 - 3/2)}] =
Follow the correct order of operations.
Do one step at a time and copy everything else each time, so you don't lose track of any operation.
= 2 - [6 ÷ 2 + {6 × 1/2 + 4/2}]
= 2 - [6 ÷ 2 + {6 × 1/2 + 2}]
= 2 - [6 ÷ 2 + {3 + 2}]
= 2 - [6 ÷ 2 + 5]
= 2 - [3 + 5]
= 2 - 8
= -6
Answer:
-6
hope this helps
Step-by-step explanation:
2_(6÷2+(6*1/2+(7/2-3/2))) solve the ones in bracket first
(7/2-3/2)=2
2-(6÷2+(6×1/2+2))
6×1/2+2
6×1/2=3
3+2=5
2-(6÷2+5)
6÷2=3
3+5=8
2-8
=-6